2020
DOI: 10.3390/life10070106
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetic Interactions between Herbal Medicines and Drugs: Their Mechanisms and Clinical Relevance

Abstract: The therapeutic efficacy of a drug or its unexpected unwanted side effects may depend on the concurrent use of a medicinal plant. In particular, constituents in the medicinal plant extracts may influence drug bioavailability, metabolism and half-life, leading to drug toxicity or failure to obtain a therapeutic response. This narrative review focuses on clinical studies improving knowledge on the ability of selected herbal medicines to influence the pharmacokinetics of co-administered drugs. Moreover, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(33 citation statements)
references
References 170 publications
0
33
0
Order By: Relevance
“…In addition, the outcomes of HDIs among different assay systems can fluctuate as a result of the multiple components in herbal extracts [58]. Multiple constituents in herbal extracts can interact or not interact individually with specific metabolic enzymes and transporters, which can also affect the PK changes to a co-administered drug.…”
Section: Responses Of a Drug's Or Herbal Product's Exposure To Differmentioning
confidence: 99%
“…In addition, the outcomes of HDIs among different assay systems can fluctuate as a result of the multiple components in herbal extracts [58]. Multiple constituents in herbal extracts can interact or not interact individually with specific metabolic enzymes and transporters, which can also affect the PK changes to a co-administered drug.…”
Section: Responses Of a Drug's Or Herbal Product's Exposure To Differmentioning
confidence: 99%
“…Several clinical studies have reported that natural compounds that have been commonly intake can affect oral availability, systemic exposure, and/or hepatic clearance of co-administered drugs for brain disorders with different mechanisms [ 46 ]. Combination of natural compounds and various drugs for brain disorders causing NDIs in clinical was summarized in Table 1 .…”
Section: Natural Compound–drug Interactions In Brain Disordersmentioning
confidence: 99%
“…In addition, the lack of knowledge on the localization of various transporters in the BBB and BCSFB of the human brain and uncertain information regarding substrates (e.g., natural compounds)–transporters complex can more hinder the exact determination of NDIs [ 110 ]. While many preclinical and clinical studies have demonstrated the potential for CYP- and/or P-gp-mediated NDIs, NDIs related with other drug transporters excepting P-gp, phase II metabolism, and transporters-mediated renal excretion are still missing [ 46 ]. Moreover, the discrepancy between in vitro estimation and in vivo studies for NDIs (i.e., lack of in vitro–in vivo correlation), and difference with animal models and humans regarding the expression of drug transporters and the consequent NDIs can also impede the exact prediction of NDIs in clinical [ 111 ].…”
Section: Challenges Of Ndis and Future Remarksmentioning
confidence: 99%
“…A secondary aim is a qualitative assessment of the attitudes toward herbal medicines expressed by authors of herb–drug interaction case reports. Review of herb–drug interaction mechanisms and extensive evaluation of individual interactions are beyond the scope of this review; the reader is referred to recent reviews by Awortwe [ 21 , 28 ], Borse [ 29 ], Chen [ 22 ], Liu [ 30 ], and Rombola [ 31 ] for further information on these topics.…”
Section: Introductionmentioning
confidence: 99%